2013
DOI: 10.1593/tlo.12364
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitization of Glioblastoma Cell Lines by the Dual PI3K and mTOR Inhibitor NVP-BEZ235 Depends on Drug-Irradiation Schedule

Abstract: Previous studies have shown that the dual phosphatidylinositide 3-kinase/mammalian target of rapamycin (PI3K/mTOR) inhibitor NVP-BEZ235 radiosensitizes tumor cells if added shortly before ionizing radiation (IR) and kept in culture medium thereafter. The present study explores the impact of inhibitor and IR schedule on the radiosensitizing ability of NVP-BEZ235 in four human glioblastoma cell lines. Two different drug-IR treatment schedules were compared. In schedule I, cells were treated with NVP-BEZ235 for 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
44
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 43 publications
15
44
2
Order By: Relevance
“…Thirty minutes after IR, Rad51 was reduced in samples treated with NVP-AUY922 alone or in combination with PI-103 under Schedule I. Twenty four hours post-IR the protein was reduced also under Schedule II after Hsp90 inhibition. In contrast to the published data on NVP-BEZ235 [26, 27], we found that PI-103 alone suppressed the expression of Rad51 only in 2 (GaMG and SW480) out of 4 tested cell lines (Figure 7). This means that the impaired DNA repair capacity revealed by the high residual histone γH2AX levels observed under Schedule II in the majority of cell lines tested cannot be explained by the depletion of Rad51 (Figure 7).…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Thirty minutes after IR, Rad51 was reduced in samples treated with NVP-AUY922 alone or in combination with PI-103 under Schedule I. Twenty four hours post-IR the protein was reduced also under Schedule II after Hsp90 inhibition. In contrast to the published data on NVP-BEZ235 [26, 27], we found that PI-103 alone suppressed the expression of Rad51 only in 2 (GaMG and SW480) out of 4 tested cell lines (Figure 7). This means that the impaired DNA repair capacity revealed by the high residual histone γH2AX levels observed under Schedule II in the majority of cell lines tested cannot be explained by the depletion of Rad51 (Figure 7).…”
Section: Resultscontrasting
confidence: 99%
“…The reason for the inhibition of Rad51 by PI-103 can be the drug-mediated G 1 arrest, similar to that reported for a different PI3K and mTOR inhibitor NVP-BEZ35 [27, 48]. It is known that Rad51 operates mostly during Homologous Recombination (HR) of DNA, which appears to be active only from the mid-S to G 2 phases of the cell cycle [49].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…To prevent radiationinducing PI3K/AKT/mTOR signaling pathway, we treated CRC cells with BEZ235 one hour before radiation and found that BEZ235 synergistically inhibited the cell viability and increased the apoptosis. Our findings are in accordance with a recent observation that the radiosensitivity of glioblastoma cells was strongly enhanced when cells were exposed to BEZ235 1 hour before radiation [35].…”
Section: Discussionsupporting
confidence: 93%
“…The PI3K pathway can be activated at different steps of the signaling cascade, most notably by loss of the phosphatase and tensin homologue (PTEN) protein, and by amplification and/or mutation of the epidermal growth factor receptor (EGFR), which occur in 40% and 50% of GBM cases, respectively (8). Accordingly, several drugs that inhibit signaling downstream of these mutations are currently in phase I and II clinical trials, either in combination with other FDA-approved chemotherapeutic agents such TMZ, or as single agents (9–13). Importantly, whereas first generation PI3K pathway inhibitors target mostly the downstream node of mTOR, the observation of feedback loops that result in enhanced PI3K signaling has led to the development of second-generation drugs (1417).…”
Section: Introductionmentioning
confidence: 99%